Analisis Pertimbangan Kemaslahatan dalam Penentuan Arah Kiblat pada Musholla Al-Qadar Surabaya - Putra, Shovan Arsya; Magfiroh, Syahriyatul; Hidayatullah, Syarif; Sanuri, Sanuri; Qulub, Siti Tatmainul (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2024)
This article aims to understand more clearly the historicity of the Al-Qadar Mosque in Surabaya. To explain this, this study uses a field method, going to the research site to interview the caretaker and several residents concerned. Data is also taken from online literacy to obtain relevant references about the direction of the qibla. This study found a problem with the direction of the qibla in the Al-Qadar Mosque and decided in terms of welfare. This mosque was initially not measured for the direction of the qibla. Then, by Eko Kunto, in 2019, the direction of the qibla was changed with the results of measurements using a compass on a smartphone and a comparison of the nearest mosque and mosque. Residents were uncomfortable with the slope of the direction of the qibla, and the place of the mosque became narrower. The caretaker decided that the direction of the qibla should be facing like the beginning of construction but tilted to the North. The decision of the mosque caretaker looked at it from a social and welfare perspective so that there would be no division and debate.